Konsepsi Metamorfosis Gondelan Sarunge Kiai Proposisi Pendidikan Islam : Indeginiutas santri Nusantara - Ngatoillah Linnaja; Robingun Suyud El Syam (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article is an attempt to find out the metamorphosis conception of the kiai's sarong gondelan, the proposition of Islamic education: the indeginiutas santri Nusantara, where the author has not found this theme before. The literature review setting is used through a qualitative descriptive approach to be further analyzed on the research subjects. The research findings show that the kiai's sarong gondelan is an education that contains an invitation to adhere to the teachings of Islam that have been taught by the kiai Nusantara, where they continue what was initiated by Walisongo. The teachings use a cultural approach that is sympathetic to the practice of Islam so that it is accepted by the Nusantara community. This researcher hopes that the results will contribute to Islamic education within the scope of teachings that describe rahmatan lil 'alamin. This research provides direction for further researchers to deepen their analysis in a wider area.